(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Thyroid function is a complex system of interrelated processes that reflect at different levels both the specificity and strength of the hormonal signal and the sensitivity of the responding tissues. Based on the analysis of literary sources, it was found that glucocorticoids affect all links of the thyroid function. At the same time, it remains relevant for researchers to study the morphometric and immunohistochemical indices of the thyroid gland, which is sensitive to homeostasis disorders, after hormonal therapy of cicatricial processes in the experimental intestine.